New Brunswick: Development of a Web-based orientation program and enhancing senior nurses' mentoring skills - Auffrey, Marise; Cormier-Daigle, Monique; Gagnon-Ouellette, Anne (Nursing Leadership, 2012)
This project to help new nurse recruits integrate into the hospital work environment had two components: the development of a new web-based orientation tool in French for new recruits and mentor training for more experienced nurses. The aim of the first component was to redesign delivery of the nursing orientation program by assessing individual needs of new recruits and developing "just in time" information sessions with online access and e-learning modules. The second component aimed to develop a voluntary mentorship training program for senior nurses that offered training on the role and responsibility of mentors. A total of 30 orientation modules were created as resources that could be adapted to the needs of each nursing unit and accessed online. Sixty nurse recruits used the programs. A mentor training program was developed, and 28 nurses were trained as mentors. The mentorship literature and guides, produced in French, will be a valuable resource for francophone nurses across Canada.

Quel avenir pour les services sociaux et de santé des communautés anglophones du Québec ? - Carter, Jane (Déclin et enjeux des communautés de langue anglaise du Québec, 2012)

The language barrier : the overlooked challenge to equitable health care - Hussey, Nadia (South African Health Review, 2012)
This chapter examines the effects of language barriers on the access of patients and communities to quality health care. It also looks at communication challenges experienced by health professionals that provide this care. Using a case study of a rural hospital, the chapter highlights some of the challenges posed by the language barrier and explores current methods that English-speaking health professionals at this hospital use to overcome these difficulties. The case study findings indicate that the language barrier decreases work efficiency and the provision of holistic treatment. It makes communication time consuming, which increases frustration levels and decreases empathy, approachability and confidentiality. Current methods for overcoming problems include the use of untrained and ineffective interpreters - usually overworked nurses; linguistic codeswitching; and the use of a selection of key isiXhosa vocabulary. These methods have many drawbacks and are not suitable or sustainable. Recommendations for improving communication include the promotion of a culture of multilingualism, which includes language education as a part of professional development and the employment of trained interpreters. For multilingualism to occur, more research needs to be conducted, and the political will to address this problem must be demonstrated. Overcoming the language barrier needs to be prioritised and commitment must be made to implementing strategies that provide a multilingual patient base with a multilingual healthcare service.

Cadre de référence pour la formation à l’offre active des services de santé en français (n°978-0-9879240-1-8) - Lortie, Lise; Lalonde, André. J. (Consortium national de formation en santé, 2012)

Reference framework: Training for active offer of French-language health services - Lortie, Lise; Lalonde, André. J. (Consortium national de formation en santé, 2012)

HR Support Kit – Pathway to Bilingual services - Regroupement des intervenantes et intervenants francophones en santé et en services sociaux de l'Ontario (2012)

Trousse d’appui RH – Vers un service bilingue - Regroupement des intervenantes et intervenants francophones en santé et en services sociaux de l'Ontario (2012)